Smart Irigasi Berbasis Arduino Sebagai Kontrol Air Subak untuk Mempertahankan Ketahanan Pangan - I Kadek Agus Wahyu Raharja; Fachri Zamzami; I Gede Feryanda Fransiska; I Gusti Ngurah Janardana (Jurnal SPEKTRUM, 2018)
Agriculture in Bali generally using Subak system as an irrigation system. This irrigation system is regulated by a traditional leader who is also a farmer in Bali. Water distribution is carried out according to the area of farmers land. The problems that can be happened on this irrigation system, such as the community that opens the floodgates to the rice fields, are not in accordance with the time provided by traditional leaders, and that can break the unity in the area. In addition, during the dry season the distribution of water is sometimes uneven because the availability of water in the dam does not meet the needs. So that Arduino-based Solar Powered Smart Irrigation is designed as one of the tools to facilitate the management of subak water distribution. The modeling made is to simulate 3 pieces of rice fields that are drained by water with the main source being the river and the source of the reserve in the form of a reservoir. This system is controlled based on the programmed time on the RTC module and the monitoring system uses the GSM SIM900 module. The data obtained is the value of water discharge in the rainy season of 2.090 L / s, the dry season of 11.18 L / s, and 0 L / s in the hard dry season.